2014
DOI: 10.1007/s00421-014-3076-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of hand and wrist muscle capacities in rock climbers

Abstract: imbalance between flexor and extensor capacities which suggests a potential risk of pathologies. Conclusions The practice of climbing not only increased the strength of climbers but also resulted in specific adaptations among hand muscles. The proposed method and the obtained data could be re-used to optimize the training programs as well as the rehabilitation processes following hand pathologies. Muscle imbalance ratio of the j joint (j = MCP or wrist) Keywords AbstractPurpose This study investigated the hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 39 publications
4
23
1
1
Order By: Relevance
“…For FE and FF muscles, the electrodes were positioned as described in Vigouroux, Goislard de Monsabert, and Berton (2015). Special attention was paid to minimize cross-talk with the nearby wrist flexors and extensors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For FE and FF muscles, the electrodes were positioned as described in Vigouroux, Goislard de Monsabert, and Berton (2015). Special attention was paid to minimize cross-talk with the nearby wrist flexors and extensors.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, these values were estimated using large climbing holds while during training and climbing, climbers mainly use small holds. Concerning the climbers' finger and forearm muscle capabilities, several previous studies revealed that climbers have high capacities for exerting maximal forces at the fingertips (Cutts & Bollen, 1993;Quaine et al, 2003;Vigouroux, Goislard de Monsabert & Berton, 2015) and minimizing fatigue effects during intermittent repetition of intense finger-grip forces (80% of maximal voluntary force, MVF) (Philippe, Wegst, Müller, Raschner, & Burtscher, 2012;Quaine et al, 2003;Usaj, 2002;Vigouroux & Quaine, 2006). Additional studies emphasised the importance of the hold depth for generating intense finger force and, by way of consequences, for climbing performances (Amca, Vigouroux, Aritan, & Berton, 2012;Bourne, Halaki, Vanwanseele, & Clarke, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A method previously used to investigate muscle capacities in rock-climbers (Vigouroux et al, 2015) has been adapted for this study. A hand-wrist ergometer (Bio2 M, Compiegne, France) measured the net isometric flexion and extension moments about the wrist and the MCP joints at 2000 Hz ( Figure 1A).…”
Section: Measurement Of Maximum Net Joint Momentsmentioning
confidence: 99%
“…Surface electrodes (9-mm diameter) were positioned over the muscle bellies after skin abrasion and cleaning with alcohol. Electrodes were placed as in Vigouroux et al, (2015) and their placement was checked by asking participants to execute a series of contractions targeting specific flexor or extensor muscle groups about either the wrist or the MCP joints. EMG signals were filtered using a Butterworth filter (bandpass, 4th order, zero phase lag, bandwidth 20-400 Hz).…”
Section: Emg Recordingsmentioning
confidence: 99%
See 1 more Smart Citation